Integrated crop-livestock systems as a solution facing the destruction of pampa and cerrado biomes in south america by intensive monoculture systems - De Moraes, Anibal; Carvalho, Paulo César de F.; Crusciol, Carlos Alexandre Costa [UNESP]; Lang, Claudete Reisdorfer; Pariz, Cristiano Magalhães [UNESP]; Deiss, Leonardo; Mark Sulc, R. (Elsevier, 2018)
While global demand for food increases, agricultural expansion faces more stringent environmental preservation demands and sustainability laws aimed to prevent deforestation (Nascente and Crusciol, 2012). Integrated crop-livestock systems (ICLS) are diversified agroecosystems that can contribute to sustainable intensification, increasing food production while maintaining or improving environmental quality and preserving natural biodiversity. A conceptual representation of ICLS can be drawn from the description of how crop and livestock activities interact. From a field- to territorial-level scale (e.g., landscape, watershed, or region), crop and livestock production can be structurally independent or interact in time and space dimensions (Moraine et al., 2016). ICLS are designed to achieve synergy and emergent properties resulting from the spatial and temporal interactions among the components soil, plant, animal, and atmosphere (Moraes et al., 2014a, b).
Keywords: Biodiversity; Degradation; Icls; Integrated; Spatial-temporal design; Sustainability